The Political Economy of Employment Regulation in Small Developing Countries - Arrowsmith, James; Parker, Jane (Relations industrielles / Industrial Relations, 2020)
It is generally accepted that employment regulation offers mechanisms to generate orderly economic growth as well as provide for the protection of workers. Both these efficiency and equity arguments particularly pertain to developing country contexts. The evolution and impact of employment law and industrial relations institutions in large developing countries is of growing interest to western scholars, but small developing countries have been ignored. This lack of research inhibits understanding of the political economy of employment regulation in developing country contexts.This article explores developments in labour regulation in three small developing countries in the South Pacific—Nauru, Tonga, and Papua New Guinea—that have been impacted by globalization and international labour regulation in different ways. The comparative research adopts a stakeholder analysis approach based on programs of qualitative interviews and documentary analysis.The paper identifies a number of structural and agency constraints on the development and effective implementation of employment regulatory systems that primarily reflect political factors. These include disorganized employment relations, under-developed civil society institutions, concentration of power networks, the under-resourcing and compartmentalization of state institutions and a broader context of political change and instability. These factors, which are related to country size as well as stage of development, subvert the introduction, implementation and review of employment regulation even where efficiency and equity arguments may be accepted by policymakers. The article concludes with a discussion of the implications and need for future research.